THE MANAGEMENT AND THE DEVELOPMENT OF THE HUMAN RESOURCES IN THE PRE-UNIVERSITY EDUCATION - Luminita, ANDONE (Strategii Manageriale)
Through the management of the human resources it is provided the necessity of the workforce in an institution, on staff categories with the view of achieving the activities and the obtaining of the expected results. The descentralization of the budget institutions makes the obtaining of some principles of the human resources management to be essential so that they create the conditions of involving and participating in the institution activity, as we wish to live in a society where the fundamental values are creativity, liberty, pluralism and tolerance. The pre-university education institution(kindergartens, schools and high schools) are not provided with a human resources manager. The descentralized management of the human resources level of the School County Inspectorate, the lack of a clear policy in the domain of the human resources ( at the level of the School County Inspectorate even if there is a management department of the human resources, those who work in this department do not have the necessary qualification, being selected teaching staff on certain criteria, and the unprofessional involvement of the local authorities, these being disruptive factors of the training-educational process.